2017
DOI: 10.25174/2249-4065/2017/70082
|View full text |Cite
|
Sign up to set email alerts
|

Status of Vulnerability in Wheat and Barley Producing States of India

Abstract: Global warming is unequivocal (IPCC, 2007) and developing countries are likely to be affected adversely by the impact of climate change (henceforth 'CC').

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…For each of these test cases, the best chemometric model and the best transformation of spectra and individual analytes were selected based on the R 2 , RMSE, bias and RPD values. We also classified both the observed and estimated soil parameters using a three‐tier STCR rating scheme generally used for Indian soils (Sendhil et al, 2018). The classification accuracy for a given parameter in the specific district and in the pooled dataset was estimated by calculating the percentage of locations for which estimated and observed values of a parameter yielded identical STCR ratings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each of these test cases, the best chemometric model and the best transformation of spectra and individual analytes were selected based on the R 2 , RMSE, bias and RPD values. We also classified both the observed and estimated soil parameters using a three‐tier STCR rating scheme generally used for Indian soils (Sendhil et al, 2018). The classification accuracy for a given parameter in the specific district and in the pooled dataset was estimated by calculating the percentage of locations for which estimated and observed values of a parameter yielded identical STCR ratings.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a meta-analysis of soil spectroscopic studies conducted between 1990 and 2019, Ahmadi et al (2021) have observed that about 69.6% of research papers used PLSR (62.3%) and modified PLSR models followed by SVR (9.9%) models. Modified PLSR models such as PLSRFS (Sarathjith et al, 2016) and PLSRLW (Gupta et al, 2018) have also been known to perform better than PLSR models (Ng et al, 2018;Dorantes et al, 2022). Therefore, we used the SVR and PLSRFS models in the remainder of this study to estimate 14 nutrient contents and corresponding SQI values.…”
Section: Collection Of Soil Spectra and Chemometric Modellingmentioning
confidence: 99%
“…The Indo-Gangetic plains (IGP) comprise north western plains zone (NWPZ) and north eastern plains zone (NEPZ) which is the major wheat tract covering around 21 million hectares, followed by central zone (CZ), peninsular zone (PZ) and northern hills zones (NHZ). The whole cropped area under wheat in India experiences heat stress under changing climatic scenario and production especially gets affected in high vulnerable central region of India (Sendhil et al, 2018(Sendhil et al, & 2017b. The CZ and PZ experiences heat stress all through the crop season and significant parts of NWPZ and NEPZ experiences terminal heat (Tiwari et al, 2017).…”
Section: Study Regionmentioning
confidence: 99%
“…Uttar Pradesh has the largest share ofthe area with 9.75 million hectares (32%), followed by Madhya Pradesh (18.75%), Punjab (11.48%), Rajasthan (9.74%), Haryana (8.36%) and Bihar (6.82%). However, a major expansion in the wheat area was observed in the states such as Jharkhand (51%), Madhya Pradesh (27%), and Rajasthan (13%) Sendhil et al (2012). State-wise comparison of area and production for 2017-2018 showsthat Uttar Pradesh, Punjab, Madhya Pradesh, and Haryana were the major contributors to the national production.…”
Section: Introductionmentioning
confidence: 99%